MODAL SOSIAL SEBAGAI STRATEGI BERTAHAN HIDUP BURUH TANI DI DESA KOPIWANGKER, KECAMATAN LANGOWAN BARAT, MINAHASA - Wolter Widyatama Hutapea; Benu Olfie L.S.; Charles R. Ngangi (Sam Ratulangi University, 2016)
This research aims to determine and describe how farm-workers can survive by social strategy as their strategy. From the three elements of social capital, that’s trust, norms, and networks, which one has the greater influence for a survival strategy of Kopiwangker farm-workers in village. This research was conducted over five months, from February until June 2016 started from preparation until making research reports. This study has used primary data and secondary data. The number of respondents is 30 respondents of whom are farm-workers. The sampling method which used in this research is purposive sampling and data analysis method used is descriptive qualitative which quantified using the Likert Scale. The results of this research indicate that social capital can be a survival strategy for Kopiwangker village farm-workers, especially on the elements of the network (patron-client networks) because it has the highest score, that is 450. But according to several informants that ever happened was also a problem among some farm-workers (as clients) and patrons, but always can be resolved.